Pro ASP.NET 1.1 in VB .NET From Professional to Expert - Moroney, Laurence; MacDonald, Matthew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
Pro ASP.NET 1.1 in VB.NET aims to be the definite reference for working developers in the field. Its compendium format covers every topic you are likely to come across in your day-to-day work, from handling data through to configuration and deployment. The books goal is to act firstly as a tutorial guide that can be read from cover-to-cover, then secondly as a reference book that you can scan quickly to retrieve the answer to a specific problem as you work. This book puts to use hard-won, real-world VB .NET experience, and demonstrates it clearly through numerous diagrams, screenshots, and working code samples.
Core Concepts -- Introducing ASP.NET -- Internet Information Services -- Visual Studio .NET -- The ASP.NET Page -- ASP.NET Controls -- ASP.NET Applications -- State Management -- Data Access -- ADO.NET Fundamentals -- Disconnected Data -- Data Binding -- Advanced ADO.NET -- XML -- Files and Streams -- Security -- The ASP.NET Security Infrastructure -- Forms Authentication -- Windows Authentication -- Authorization -- Advanced Security -- Advanced User Interface -- User Controls -- Custom Server Controls -- Design-Time Support -- JavaScript -- Dynamic Graphics with GDI+ -- Web Services -- Creating Web Services -- Web Service Standards and Extensions -- Advanced Web Services.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems